PENYULUHAN POSYANDU DAN SENAM SEHAT UNTUK LANSIA DI RT 13 DUSUN TALANG KELAPA - Mayreista, Dita; Novianti, Rahmi; Peno, Arka; Jeklin, Jeklin; Pebrisandra, Adelia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2023)
Community service activities use counseling and outreach methods, with the target participants being the elderly group. Posyandu counseling and healthy exercise for the elderly have been carried out at RT 13 Talang Kelapa Hamlet for 5 (five) days. The results of the service activities, namely posyandu counseling, were attended by 21 (twenty one) participants from the elderly group, and health workers from the Community Health Center. This activity consists of a discussion about the importance of health care for the elderly and free health checks. Furthermore, there are healthy exercise activities for the elderly which provide benefits for the health of the elderly, including improving the health of the heart and cardiovascular system, increasing physical fitness, reducing the risk of chronic disease, improving mental and emotional health for the elderly, improving the quality of life of the elderly, and improving the social relations of the elderly with others.